Problem-Based Learning in Elementary Schools: The Study Of Curiosity and Mathematics Communication Ability - Pramiasari, Apdika Dwi; Muslim, Arifin; Supriatna, Supriatna (Journal of Innovation and Research in Primary Education, 2022)
Curiosity and mathematical communication are important aspects that students must have in learning mathematics. However, many studies show that students' mathematical curiosity and communication are still low. For this reason, it is important to instil this ability in students from the time they take basic education. This study aims to increase students' curiosity and students' mathematical communication skills through the Problem Based Learning model for elementary school students. This research is a classroom action research conducted in 2 cycles, each cycle consists of 2 meetings. The subjects of this class action research were class IV students, totalling 32 students consisting of 13 male students and 19 female students. Data collection tools using tests and non-tests. The results of the observation of the curiosity of students in the first cycle are 69.05% with good criteria and in the second cycle is 84.95% with very good criteria. The results of the mathematical communication ability test of students in the first cycle were 74.06 with good criteria and in the second cycle, 84.2 with very good criteria. The results of observing teacher activities in the first cycle were 71.3% with good criteria and in the second cycle, 90.45% with very good criteria. The results of observing student activities in the first cycle were 63.5% with good criteria and in the second cycle 89.75% with very good criteria. The results of this study indicate that using the Problem Based Learning (PBL) model can increase the curiosity and mathematical communication skills of students in statistical material in class IV SD Negeri 1 Contributing.